2022
DOI: 10.1109/access.2022.3168679
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Subwavelength Periodic Microstrip Guard Trace in High-Speed Circuits

Abstract: This paper proposed a kind of guard traces based on a subwavelength periodic structure to reduce the far-end crosstalk (FEXT) of parallel microstrip lines in the PCB. This technology can be used to improve the false triggering and signal transmitting capacity of a multiconductor transmission line circuit system. In order to explore the present novel guard trace effect on isolating electromagnetic interference (EMI), the frequency response of the mutual capacitance and mutual inductance of the overall circuit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…PCB design engineers reduce areas of circuit boards with various periodically distributed serpentine delay lines [11], [12]. In addition, periodic serpentine lines or periodic microstrip lines can be introduced between two parallel microstrip lines to block electromagnetic interference between two signal traces [13]- [15]. Recent studies have found that periodic structures etched on metal surfaces lead to new guided-wave modes [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…PCB design engineers reduce areas of circuit boards with various periodically distributed serpentine delay lines [11], [12]. In addition, periodic serpentine lines or periodic microstrip lines can be introduced between two parallel microstrip lines to block electromagnetic interference between two signal traces [13]- [15]. Recent studies have found that periodic structures etched on metal surfaces lead to new guided-wave modes [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al added graphene paraffin material to the signal line with labels to suppress FEXT [10] and increased the cost of batch production. Ma et al proposed a kind of guard trace based on a subwavelength periodic structure to reduce the FEXT of parallel microstrip lines [11] and limit the high-density layout. In 2015, Intel Corporation proposed a non-uniform transmission line that can reduce crosstalk and meet the requirements of high-speed and high-density integration.…”
Section: Introductionmentioning
confidence: 99%
“…Several new circuit structures and circuit models that may use SPMLs to suppress the crosstalk between adjacent microstrip lines have been suggested [29][30][31]. Since the electromagnetic coupling between CML and SPML is very weak, if SPMLs were used as the guard traces of high speed circuits, the total number of grounded holes of the guard traces can be significantly reduced [32] and this does not affect the wiring of other layers in circuit boards.…”
Section: Introductionmentioning
confidence: 99%